The Effect of “Sharing Content through Ignorant Actions” in Digital Media, Youtube on the Formation of Middle Society Attitudes Case Study: Youtube Baim Paula - Taffani Rahma Yuandara; Irwansyah Irwansyah (Budapest International Research and Critics University, 2021)
The rapid development of digital media with increasingly diverse features makes its users increasingly pampered in accommodating the needs of sharing messages. The widespread use of social media is often used as a field to earn rupiah by its users, various ways is used to make content variations in each channel and channel owned. The most used channel is YouTube. Baim Wong on his YouTube channel and shared in several videos about sharing done with mischief. This social experiment is also carried out by sharing actions that use more fun ways, through disguises, humorous scenes, to those that are closed with social actions. This research was conducted with a qualitative approach using a literature review methodology or literature study. The literature review was carried out by looking at digital content and the impact it had. This research is to find out how the shared content is able to influence the attitude formation of the middle class.